Improving Learning Activities and Learning Outcomes Indonesian Using a Cooperative Model - Perangin-Angin, Roslina; Kartolo, Rahmat; Ginting, Sri Ulina Beru (Journal of English Language and Education, 2025)
This study aims to find out whether using a cooperative model can improve student activities and learning outcomes. This type of research is a 2-cycle quantitative research and assessment consisting of 4 stages, namely planning, implementation, observation and reflection. This research was conducted at the State Elementary School 060939 Medan Amplas District for the 2024-2025 Academic Year. Where it involves grade V students as research subjects, while the object of research is to improve student activities and learning outcomes on the ability to understand narrative discourse. This research instrument uses observation sheets and students' written tests in the teaching and learning process. The results of this study show that the implementation of cooperative learning can improve the activities and learning outcomes of students in grade V of SD Negeri 060939 Medan Amplas District for the 2024-2025 Academic Year. This can be seen from the results of observation of student activity in the first cycle of 73.3% and in the second cycle of 84.6%. Meanwhile, the improvement in learning outcomes was obtained from the results of the action test of each cycle, and the first cycle of classical learning outcomes was 71.42%, and the completeness of classical learning outcomes in the second cycle was 89.28%. Therefore, it can be concluded that using a cooperative model can improve the activities and learning outcomes of Indonesian students in class V of SD Negeri 060939 Medan Amplas District for the 2024-2025 Academic Year.